From Dunoon to Dunedin: What two distant charitable cookbooks reveal about the British tradition of soups - Leach, Helen (Petits Propos Culinaires, 2006)
The author describes two charity cookbooks both dating from 1905, one published in New Zealand and the other in Scotland. Surprisingly, they both had quite a lot in common.